Quality of Public Services in The Population and Civil Registration Office of Minahasa Regency - Tumewu, Wandri; Bogar, Wilson; Mandagi, Marthinus (Technium Social Sciences Journal, 2023)
This research aims to analyze the quality of service in issuing family cards at the Population and Civil Registration Service of Minahasa Regency. This research used qualitative research methods, and 4 (four) informants were interviewed. The results of existing research show that the quality of service available for issuing family cards at the Population and Civil Registration Service of Minahasa Regency is still not optimal, because based on the results of research data, it was found that there are still delays in issuing family cards, which can take weeks or months. Then there are still various obstacles in processing the issuance of Family Cards, such as community power outages, internet or computer network problems. In fact, the public does not know and understand the conditions required for issuing a Family Card. In fact, there is still a lack of socialization regarding the requirements for issuing Family Cards to the community and existing human resources are still very lacking. Furthermore, there is still a shortage of Family Card forms at the Minahasa Regency Population and Civil Registration Service.